Driving Nvidia’s Market Value: The Roles of ROA, Current Ratio, and Debt to Equity Ratio - Aulia Rahman; Taufik Sadikin; Dudi Hendaryan (Journal of Educational Management Research, 2026)
This study aims to examine the effects of Return on Assets (ROA), Current Ratio (CR), and Debt to Equity Ratio (DER) on stock prices during the period 2015–2025. The research employed a quantitative explanatory approach using quarterly financial statement and stock price data, resulting in 44 observations. Data were analyzed using multiple linear regression with HAC (Newey–West) standard errors to address autocorrelation issues in time-series data. Prior to hypothesis testing, classical assumption tests including normality, multicollinearity, heteroscedasticity, and autocorrelation tests were conducted. The findings reveal that Return on Assets (ROA) has a positive and significant effect on stock prices, indicating that profitability remains a key factor influencing investor valuation. Debt to Equity Ratio (DER) also demonstrates a positive and significant effect, suggesting that leverage is perceived as a strategic financing instrument supporting growth opportunities. In contrast, Current Ratio (CR) does not significantly affect stock prices, implying that liquidity information is less relevant to investors compared to profitability and growth prospects. Simultaneously, ROA, CR, and DER significantly influence stock prices, with an adjusted R² of 72.49%. The study contributes to the literature by highlighting the differing relevance of financial ratios in technology-driven firms and supports Signaling Theory, Trade-off Theory, and Adaptive Market Hypothesis in explaining investor behavior during periods of technological transformation.